Investment Analysis in Financial Management (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In the article the research of interrelation investment analysis and modern financial management. Analyzed theoretical approaches to the definition of an investment analysis across using methods of analysis of investment activities and the complex components of the investment analysis in financial management, which is formed on the causal relations of the economic processes and phenomena in the investment activities using the totality of right financial management decisions. The main components and functions of investment analysis in financial management on the basis of which it is possible to systematically evaluate the advantages and disadvantages of investment projects through the establishment of the logical schemes of management on the basis of the search for common sides and differences of components of investment analysis and financial management
Keywords: finance, management, financial management, investments, analysis, investment activity, investment analysis, investment analysis in financial management